ChemInform Abstract: Synthesis of Fluorescent 2, 6‐Dicyano‐3, 5‐disubstituted Anilines Using Cellulose Sulfuric Acid in Aqueous Media. Issue 40 (September 2016) - Zonouzi, Afsaneh; Izakian, Zakieh; Abdi, Khosrou; Ng, Seik Weng
Abstract: Title compounds are synthesized from an 1, 3‐diketone and three equivalents of malononitrile using cellulose sulfuric acid as catalyst, and in the presence of a secondary amine which is essential.